HUBUNGAN KONDISI LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN PNEUMONIA PADA ANAK BALITA DI KECAMATAN PACITAN KABUPATEN PACITAN - Delima Kurnia Sari; Mursid Rahardjo; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
During the last 3 years the incidence of pneumonia in Pacitan District fluctuated. The highest pneumonia incidence in 2017 was in Pacitan subdistrict with 146 cases with incident rate in 2017 was 38 per 1000 children. This study aimed to analyze the physical environmental of house factors associated with pneumonia in under-five children in Pacitan district. This research used observational analytic study with case control design. Samples in this research were 80 children aged 12-59 months consisting of 40 case groups and 40 control group with age and sex of the children matching. Analysis of data using chi square test and Odds Ratio (OR). The result showed the majority of respondents' houses had wall types, occupancy density, proportion of house ventilation that fulfilled the requirements. Respondent's house has a range of room temperature ranging from 26.3 ºC -32.8 ºC and room humidity level 47.5% -77%. There were 4 related variables from 9 variabels such as the presence of family members who smoked (p-value=0,035; OR=3,116; 95%CI=1,184-8,200), use of mosquito coils (p-value=0,034; OR=9,750; 95%CI=1,158-82,108), type of floor (p-value=0,042; OR=3,400; 95%CI=1,156-9,996) and lighting intensity (p-value=0,001; OR=7,364; 95%CI=2,204-24,602). It can be concluded that there is a relationship between condition of physical environment at home with pneumonia in children under five years in Pacitan district.